Scaffolding learning from molecular visualizations. Issue 7 (31st May 2013) - Chang, Hsin‐Yi; Linn, Marcia C.
Abstract Powerful online visualizations can make unobservable scientific phenomena visible and improve student understanding. Instead, they often confuse or mislead students. To clarify the impact of molecular visualizations for middle school students we explored three design variations implemented in a Web‐based Inquiry Science Environment (WISE) unit on thermodynamics: Observation, Research Guidance, or Critique. We tested these variations in an inquiry unit designed following the knowledge integration framework to promote coherent understanding. Seven middle school classes (205 students) and their two teachers participated in the study. Students studying each version of the unit made significant gains on knowledge integration items designed to measure coherent understanding of thermodynamics. Compared to Research Guidance, the Critique condition was more successful, especially in helping students conduct consequential experiments. Embedded assessments revealed that students who critiqued a confounded experiment were more successful in conducting valid experiments than students who did not critique. In addition, the combination of critique and virtual experimentation increased student ability to connect molecular and observable phenomena. These results suggest design guidelines to help future designers. Specifically, preceding experimentation with critique activities helps students distinguish among existing and new ideas. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50: 858–886, 2013